Pengembangan Lembar Kerja Peserta Didik Berbasis Problem-Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Fadilah Rahmayuni Nasution; E. Elvis Napitupulu (Universitas Palangka Raya, 2023)
This research aims to produce a product in the form of problem-based learning worksheets (LKPD) that is valid, practical, and effective to improve students' mathematical problem solving skills. This research is designed based on the stages of the 4-D development model by Thiagarajan, Semmel, and Semmel which are adapted into 3-D including the stages of define, design, and develop. The subjects in this study were 31 students of grade VII-4 SMP Negeri 2 Percut Sei Tuan. Based on the research that has been conducted, the validity of the developed LKPD obtained an average percentage of assessment of 84.1% by experts with qualifications classified as very valid. Through the LKPD practicality questionnaire by teachers and students, an average percentage of assessment was obtained of 90% by teachers and 93.6% by students with qualifications classified as very practical to be used in the learning process. The implementation of learning with the application of problem-based learning LKPD has been carried out to see the effectiveness of LKPD with assessment references that are determined to obtain results, namely for the completeness of classical learning reaching 83.9%, the achievement of learning objectives is achieved in question points 1, 2, 3, 4, and 5, and the achievement of efficient learning time or does not exceed ordinary learning. From the three references for assessing effectiveness, the LKPD developed is classified as effective. The increasing in mathematical problem solving was in the medium category with an average gain score of 0.60. Based on the research acquisition data, it is concluded that the problem-based learning LKPD developed in this study has met valid, practical, and effective qualifications.